Review: A Male President for Mt. Holyoke College: The Failed Fight to Maintain Female Leadership, 1934-1937 by Ann Karus Meeropol - Frinde Maher (Radical Teacher, 2014)
Review of A Male President for Mt. Holyoke College: The Failed Fight to Maintain Female Leadership, 1934-1937 by Ann Karus Meeropol.